Social Behavior of Children with Mental DIsable in Physical Education Learning - Wulan Sari; Gita Febria Friskawati; Diky Hadyansyah (STKIP Pasundan Press, 2026)
This research on the social behavior of students with tunagrahita in physical education learning departs from the ignorance of the social behavior of children with special needs which is influenced by various factors. Therefore, the purpose of this research is to find out the social behavior shown by children with disabilities in physical education learning. The research method used is descriptive qualitative with a non-participatory observation approach. The population in this study were children with tunagrahita in SLB Hanjuang Jaya. The sample was selected purposively selected as many as four children with tunagrahita. The analysis technique used is reduce data, display data, verify, and interpret the meeting. The result showed that the most children with tunagrahita, especially those in the mild category, showed social behavior as a result of habituation. Whereas children with moderate category can show some social behavior when learning physical education.